2023
DOI: 10.17478/jegys.1246237
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of body posture problems experienced in baglama teaching process

Abstract: Bu araştırma, bağlama öğretim sürecinde yaşanan bedensel kurulum sorunlarının neler olduğunu belirlemek ve bu sorunların giderilmesine yönelik çözüm arayışlarını ortaya çıkarmak amacıyla yapıldı. Araştırma nitel araştırma yöntemine uygun olarak gerçekleştirildi. Araştırmanın katılımcılarını % 88,1’si erkek (n=37), % 11,9’i kadın (n=5) olmak üzere toplam 42 bağlama çalgı öğretmeni oluşturdu. Çalışmada veri toplama aracı olarak araştırmacı tarafından hazırlanan “açık ve kapalı uçlu anket formu” kullanıldı. Elde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
2
0
2
Order By: Relevance
“…The bodily setup stage consists of sub-steps such as posture, sitting, positioning the bağlama on the body, the position of the hands and arms in relation to the bağlama, and the grip of the pick if techniques with the pick are to be taught (Karahan, 2010;Akçalı, 2012;İnanıcı, 2023). It has been observed that the taxonomic preferences of the authors regarding the teaching of the sub-steps of bodily setup in their materials can differ from each other and vary considerably.…”
Section: Discussion and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The bodily setup stage consists of sub-steps such as posture, sitting, positioning the bağlama on the body, the position of the hands and arms in relation to the bağlama, and the grip of the pick if techniques with the pick are to be taught (Karahan, 2010;Akçalı, 2012;İnanıcı, 2023). It has been observed that the taxonomic preferences of the authors regarding the teaching of the sub-steps of bodily setup in their materials can differ from each other and vary considerably.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…When analyzing the literature on instrument teaching, the most basic step of the initial stage of instrument learning is learning the bodily setup. The bodily setup stage is the most basic step in the initial process of instrument teaching (Karahan, 2010;İnanıcı, 2023). "Body posture is the bringing of a part of the body, arm, hand, fingers or all of them into the desired shape for a certain behavior to take place" (İnanıcı, 2023, p. 92).…”
Section: Bodily Setupmentioning
confidence: 99%
See 2 more Smart Citations